The Sphere Project humanitarian charter and minimum standards in humanitarian response - The Sphere Project (The Sphere Project, 2011)
The Sphere Project is an initiative to determine and promote standards by which the global community responds to the plight of people affected by disasters.
Keywords: Disasters